Psychological Support in Uplifting University Students’ Happiness in Fighting the Coronavirus Lockdown - Getrude Cosmas (2020)
The coronavirus pandemic has caused turbulence in the lives of several university students around the globe, including students of University Malaysia Sabah. The first 14 days ofthe coronavirus lockdown delivered significant psychological experiences to university students.Data from 106 on-and off-campus university students were examined to explore the effects of resiliency coping skills and religious faith in uplifting happiness in students after the first 14-day of the coronavirus lockdown. Also, the effects of religious faith on resiliency were examined. Out of 106 students, 74 (69.80%) were female and 32 (30.20%) were male. The study demonstrates that students‟ resiliency contributed 15% to the variance of happiness, while religious faith contributed 4% to the variance of resiliency. Furthermore, the on-campus students were more resilient compared to off-campus students. High resilient copers were also happier than low-and medium resilient copers. These findings give a glimpse of hope that the